Heritage waste management: A possible paradigm shift in the post-earthquake reconstruction in central Italy. Issue 1 (28th November 2019) - Shirvani Dastgerdi, Ahmadreza; Stimilli, Flavio; Pisano, Carlo; Sargolini, Massimo; De Luca, Giuseppe
Abstract : Purpose: The considerable volume of rubble generated by the 2016–2017 earthquakes in central Italy reveals a significant issue in the post-disaster reconstruction phase. Drawing from the experience of Macerata province and the city of Camerino, the purpose of this paper is to explore a possible change of attitude in the reuse of heritage waste materials in the reconstruction process of damaged historical villages and towns in Italy. Design/methodology/approach: This research outlines a comparison between national and regional directives on the rubble management on the one hand, and the praxis on the other, carrying out semi-structured interviews with experts who have been involved in the reconstruction process of Macerata province and Camerino, in Marche region. Findings: The research reveals that the current vision in Italy for the management of disaster waste is still very close to the traditional paradigm that gives heritage waste an intrinsic value, worthy of great efforts for its collection, catalogue and preservation in view of the likely philological restoration of the damaged heritage. The most recent experiences in Camerino show that institutions responsible for the conservation of cultural heritage may accept a possible paradigm shift towards a more innovative and less expert-driven approach to heritage waste materials and their possible upcycling. Originality/value: Within a critique of the traditional restoration paradigm, this article links disaster waste management to the Sendai Framework for Disaster Risk Reduction, to enhance the long-term sustainability of historical villages and towns in Italy.